Handbook on climate change and agriculture - Mendelsohn, Robert O., 1952-; Dinar, Ariel, 1947-; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar, 2011)
This book explores the interaction between climate change and the agriculture sector. Agriculture is essential to the livelihood of people and nations, especially in the developing world; therefore, any impact on it will have significant economic, social, and political ramifications. Scholars from around the world and from various fields have been brought together to explore this important topic.
pt. 1. Agronomic studies of climate impacts and adaptation -- pt. 2. Economic studies of climate impacts on agriculture -- pt. 3. Agricultural impacts on the economy -- pt. 4. Agricultural mitigation -- pt. 5. Adaptation to agricultural impacts.
Includes bibliographical references and index.
Keywords: Agriculture -- Environmental aspects; Climatic changes -- Economic aspects; Electronic books